Tomografia de coerência óptica: medida da espessura do subcampo central no edema macular diabético - HONNOUCHE, Rosana Zacarias (2011)
Diabetic macular edema (DME) is the main cause of visual loss in diabetic patients and is characterized by retinal thickening, whose evaluation is important for the diagnosis and management of diabetic retinopathy. The aim of this research was to measure the central subfield thickness (CST), the best-corrected visual acuity (BCVA) and the macular volume, and compare these data to those of diabetic patients without DME, using spectral-domain optical coherence tomography (SD-OCT), for quantitative analysis of DME.Two hundred patients with nonproliferative diabetic retinopathy (NPDR) were enrolled in a transversal study, from which 55 eyes with macular edema were detected by fundus biomicroscopy. Twenty seven diabetic patients without DME and with normal ophthalmological exam served as control group. Measurements of CST (main variable), BCVA and macular volume were taken, considering the variables age, gender, NPDR classification, external limitant membrane (ELM) integrity and type of DME. Biomicroscopy with noncontact lens, fluorescein angiography and spectral optical coherence tomography were performed using Cirrus SD-OCT. Besides descriptive statistics, additional tests were applied to analyze the results, such as variance analysis, t-Student, chisquare, Fischer s exact test, Mann-Whitney and Kruskall-Wallis. The relation between CST and BCVA was studied by linear regression, with logarithmic scale of minimal angle of resolution (logMAR). It was found that there is no significant difference between case and control groups for the variables age and gender. However, there was significant difference for variables CST, BCVA and macular volume. It was found significant correlation between retinopathy severity according to NPDR classification and the mean value of CST,which is the greater the retinopathy severity, the greater the CST. Most of the patients presented moderate NPDR. A strong correlation between macular volume and CST was found. Patients with serous retinal detachment presented higher mean value of CST, and those with CME presented worse BCVA. Patients with disrupted ELM showed greater mean value of CST and worse BCVA. It was concluded that SD-OCT allows quantitative measurement of CST in DME and, for identifying the retinal layers individually, also detects retinal structural changes and correlates them to visual functions.